2020
DOI: 10.3390/cancers12123559
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Externally Activated Nanoparticles for Cancer Therapy

Abstract: Nanoparticles activated by external beams, such as ionizing radiation, laser light, or magnetic fields, have attracted significant research interest as a possible modality for treating solid tumors. From producing hyperthermic conditions to generating reactive oxygen species, a wide range of externally activated mechanisms have been explored for producing cytotoxicity within tumors with high spatiotemporal control. To further improve tumoricidal effects, recent trends in the literature have focused on stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…There are several physical approaches for inducing hyperthermia, including electromagnetic radiation, ultrasound, hyperthermic perfusion, and conductive heating [ 10 ]. Nanoparticles with appropriate external energy sources are being used for local treatment [ 45 , 46 , 47 ]. Strategies to enhance the therapeutic efficacy of hyperthermia are also under investigation; in this context cytotoxic properties of hyperthermia on leukemia, melanoma, lung carcinoma, and colon cancer cells, among others, have been improved by the use of compounds that sensitize to the cells [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several physical approaches for inducing hyperthermia, including electromagnetic radiation, ultrasound, hyperthermic perfusion, and conductive heating [ 10 ]. Nanoparticles with appropriate external energy sources are being used for local treatment [ 45 , 46 , 47 ]. Strategies to enhance the therapeutic efficacy of hyperthermia are also under investigation; in this context cytotoxic properties of hyperthermia on leukemia, melanoma, lung carcinoma, and colon cancer cells, among others, have been improved by the use of compounds that sensitize to the cells [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The next limitation is that the physiological response of nano-carriers is yet not very well understood. For example, studies showed that the crystalline silver nanoparticles might cause cytotoxicity in the human fibroblasts, keratinocytes, lesioned skin [31]. Liposomal vesicles can be arrested by the immune system [32].…”
Section: Limitations Of Nanoparticles In Drug-delivery Systemmentioning
confidence: 99%
“…where (ηC, ηS) and (ρC, ρS) are the corresponding fractions of diminished mass and densities of the core Fe3O4 and shell GA, respectively. Using the parameters ηC = 0.75 and ηS = 0.25 obtained from Figure 4) for MNP-GA1, as well as ρC = 5.18 g/cm 3 and ρS = 1.4 g/cm 3 as the densities of Fe3O4 and GA, respectively, it is estimated that ΔMNP-GA1 = 1.7 nm. In the same way, using ηC = 0.84 and ηS = 0.16, the thickness for MNP-GA2 is ΔMNP-GA2 = 1.1 nm.…”
Section: Physicochemical Characterization Of the Ga-coated Mnpsmentioning
confidence: 99%
“…The corresponding values are depicted in Figure 7b. Due to the small value of η, the parameter P involves ρ FF = 1.0 g/cm 3 and c v = 4.18 J/(kg × K) which are the same as water. Additionally, Figure 7b shows the regression of the experimental measurements, fitting the mathematical expression P = B × H 2 and getting B = 0.2 W/(cm 3 Am −1 ) 2 as the proportionality constant (with R 2 = 0.999 of correlation).…”
Section: Physicochemical Characterization Of the Ga-coated Mnpsmentioning
confidence: 99%
See 1 more Smart Citation